Mediating Role of Job Satisfaction in The Influence of Organizational Culture and Incentive and Rewards on Employee Performance - Lydia Gracia Theodora; Justine Tanuwijaya; Andreas Wahyu Gunawan Putra (Universitas Muhammadiyah Enrekang, 2023)
This study aims to examine the effect of organizational culture and incentives and rewards on employee performance mediated by job satisfaction. The data used in this study is primary data. A total of 104 employees were used in the study using the saturation sampling technique. Research data were analyzed by descriptive analysis and hypothesis testing using the Structural Equation Model (SEM) with AMOS 22 software. The results showed that organizational culture variables had no effect on job satisfaction, incentive and rewards variables had a positive effect on job satisfaction, organizational culture variables had a positive effect on employees performance, incentive and rewards variables have no effect on job performance, job satisfaction is able to mediate organizational culture and incentives and rewards which have a positive impact on employee performance.